Convergence analysis of the unpunctured turbo trellis-coded modulation (UTTCM) - Ahmed Haffane; Abdelhafid Hasni; Mustapha Khelifi; Boufeldja Kadri (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, the performance of the Unpunctured Turbo Trellis-Coded Modulation (UTTCM) over Additive White Gaussian Noise (AWGN) channel is analyzed using the non-binary extrinsic information transfer (EXIT) chart. The exchange of the extrinsic information between the decoder components is tracked, allowing the generation of an EXIT chart, which is a powerful tool for analyzing the convergence behavior of iterative decoding and prediction of convergence position. The Simulation results are compared with the turbo cliff positions on the BER curves.